Implementation of Monsakun Problem-Posing to Enhance Elementary School Students' Conceptual Understanding of Mathematics in Indonesia - Rico Valentino; Munir Munir; Herbert Siregar (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
This study was conducted to develop Monsakun, a web-based Problem Posing learning platform, through the Research and Development (R&D) method using the 4D model: Define, Design, Develop, and Disseminate. The main objective of this research is to create an interactive and effective learning tool that enhances students' ability to understand and apply concepts through systematic Problem Posing activities. The study responds to existing challenges in Problem Posing-based learning, which is often perceived as less engaging and insufficient in nurturing students' critical thinking and creativity. The research procedures included a comprehensive needs analysis, prototype design, product development, and testing for effectiveness. User experience was measured using the User Experience Questionnaire (UEQ) and System Usability Scale (SUS). The results indicated that Monsakun received an